Bio-reinforcement for improving shear strength in road embankments towards eco-friendly soil stabilization and sustainable infrastructure - S. Chezhiyan; K. Sudalaimuthu (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The stability of road embankments is a critical aspect of sustainable infrastructure. Insufficient shear strength in soil can lead to slope failure, often exacerbated by vehicular loads and surface erosion from heavy, prolonged rainstorms. Traditional soil stabilization methods frequently involve synthetic materials, which may have adverse environmental impacts. The objective of this study is to investigate the potential of bio-reinforcement using Vetiver grass roots to enhance the shear strength of soils in road embankments, providing an eco-friendly alternative for soil stabilization.METHODS: Sixteen undisturbed soil samples were collected from two distinct locations on a road embankment with different soil types. Both unreinforced and bio-reinforced samples were subjected to a series of direct shear tests. The bio-reinforced samples were collected three months after Vetiver grass was planted on the slopes of the Rasipuram bypass road embankment. Shear strength parameters, including cohesion and the angle of internal friction, were determined and compared between unreinforced and bio-reinforced soils.FINDINGS: The findings indicated a significant improvement in the shear strength of the soil due to bio-reinforcement. In Location 1, the bio-reinforced soil showed a 48 percent to 64 percent increase in shear strength across different normal stresses, averaging a 53 percent improvement. In Location 2, the improvement ranged from 34 percent  to 115 percent, with an average increase of 67 percent. The cohesion of bio-reinforced soil in Location 1 increased from 5.23 to 11.52 kilonewtons per square meter, while in Location 2, it rose from 10.56 to 24.52 kilonewtons per square meter. The angle of internal friction improved from 20.07 to 27.42 degrees in Location 1 and from 17.73 to 23.22 degrees in Location 2.CONCLUSION: This study concludes that bio-reinforcement with Vetiver grass significantly enhances the shear strength of soils, making it a viable and sustainable method for road embankment stabilization. The improvements in cohesion and the angle of internal friction indicates that Vetiver grass can effectively increase soil stability, offering an eco-friendly alternative to traditional soil stabilization methods. The findings ensure a healthy soil and plant environment, highlighting the role of Vetiver grass in improving soil properties and stability, and showcasing an eco-friendly solution for sustainable infrastructure development. This study supports the broader application of bio-reinforcement in infrastructure projects, contributing to specific sustainable development goals such as sustainable development goals 9 (Industry, Innovation, and Infrastructure) and sustainable development goals 15 (Life on Land).